2012
DOI: 10.1007/s10508-012-9904-z
|View full text |Cite
|
Sign up to set email alerts
|

Risky Sex: Interactions Among Ethnicity, Sexual Sensation Seeking, Sexual Inhibition, and Sexual Excitation

Abstract: Rates of sexually transmitted infections, including HIV, vary across ethnic minority groups, yet few studies have evaluated sexual risk behaviors and their psychological correlates to determine if risk and protective factors vary by ethnicity. The purpose of the current study was to assess sexual sensation seeking (SSS), sexual inhibition (SIS1 and SIS2), and sexual excitation (SES) as correlates of risky sexual behaviors in 106 (55 male and 51 female) Asian Americans, African Americans, and Caucasian American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 19 publications
4
15
0
2
Order By: Relevance
“…However, there have been discrepant results for HAI among heterosexuals. One study among heterosexuals found that SSS was associated with number of anal sex partners, but their emphasis was on ethnicity (Nguyen et al, 2012). Another study found no correlation between HAI and SSS among heterosexual men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there have been discrepant results for HAI among heterosexuals. One study among heterosexuals found that SSS was associated with number of anal sex partners, but their emphasis was on ethnicity (Nguyen et al, 2012). Another study found no correlation between HAI and SSS among heterosexual men.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study was conducted among a sample of mostly white college students, and the findings may not be true of other populations. Another study conducted in a sample of heterosexual sex-research volunteers found a positive correlation between SSS and number of anal sex partners among Asian Americans and Caucasians, but no association among African Americans (Nguyen et al, 2012). In this study analyses were not stratified by gender.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, high scores on SIS2 have generally been significant negative predictors of high-risk sexual activity [93]. Recent studies have also shown that dual-control processes have been associated with sexual sensation seeking [94], a trait that has been defined as the need for varied, novel, and complex experiences and sensations. Sexual sensation seeking has also been linked closely with impulsive decision making and risky sexual behavior [95,96].…”
Section: A Theoretical Model Of Sexuality Impulsivitymentioning
confidence: 99%
“…Recent research has indicated that lower rates for Hispanics may be due to high levels of acculturation and religiosity (Smith, 2015). Asian populations have been highly understudied in the sexual risk research (Nguyen et al, 2012; So, Wong, & DeLeon, 2005) as they have one of the lowest rates of HIV infection (Centers for Disease Control Prevention, 2013). therefore, research on changing behavior to prevent HIV and other STDs is of great importance.…”
Section: Introductionmentioning
confidence: 99%